THE EFFECT OF CASE-BASED LEARNING MODEL WITH AUGMENTED REALITY MEDIA ON LEARNING OUTCOMES AND STUDENTS' CREATIVE THINKING SKILLS - Lisa Mulyani; Herliani Herliani; Elsje Theodora Maasawet; Sri Purwati (Universitas Negeri Makassar, 2024)
This research aims to determine the effect of the application of the Case Based Learning model with Augmented Reality Media on creative thinking skills and learning outcomes on human immune system material of grade XI students at SMA Negeri 8 Samarinda. The type of research is a quasi-experimental design with a research design of Nonequivalent Control Group Design. Sampling using purposive sampling technique with a sample size of 50 students. Data analysis techniques using descriptive data analysis, N-Gain test and Independent sample t-test. The results of data analysis showed that the percentage of creative thinking skills measured based on indicators in the experimental class was 70% in the high category and 56% control class in the moderate category. The N-Gain test of learning outcomes obtained is in the experimental class 0.4 medium category and the control class is 0.31 medium category. The hypothesis results show a significance of 0.000 which is smaller than 0.05 so it can be concluded that there is a significant effect on the application of the Case Based Learning model assisted by Augmented Reality Media on the creative thinking ability and learning outcomes of class XI students at SMA Negeri 8 Samarinda.